Association between Diagonal Earlobe Crease and Cardio-Ankle Vascular Index in Asymptomatic Hypertensive Patients - Korkmaz, Levent (Med Princ Pract, 2013)
OBJECTIVE: The aim of this study was to investigate the association between earlobe crease (ELC) and cardio-ankle vascular index (CAVI) in asymptomatic hypertensive subjects. MATERIALS AND METHODS: A total of 75 subjects with ELC and 75 age- and gender-matched patients without ELC were prospectively selected from subjects admitted to the Outpatient Cardiology Clinic. ELC was assigned to a person with a crease stretching obliquely from the outer ear canal towards the border of the earlobe of at least one ear. CAVI was assessed by a VaSera VS-1000 instrument. RESULTS: There were statistically significant higher CAVI values in ELC subjects (9.8 ± 2.1 vs. 8.6 ± 1.6, p < 0.001). There was a significant and positive association between CAVI and age (r = 0.42, p < 0.001), ELC (r = 0.31, p < 0.001), BMI (0.20, p < 0.001) and male gender (r = 0.21, p = 0.04). Linear regression analysis demonstrated ELC (95% confidence interval, CI, 0.61–1.74, p = 0.009), age (95% CI 0.03–0.09, p < 0.001) and male gender (95% CI 0.48–1.55, p = 0.03) as independent determinants of CAVI. Also, there was a higher prevalence of ELC in subjects with subclinical atherosclerosis (CAVI ≥9) than in normal subjects (CAVI <9). CONCLUSION: Patients with ELC had higher CAVI than normal subjects. This observation of ELC is simple, adds no cost and can be easily made by most physicians, and it may provide important predictive information of arterial stiffness and subclinical atherosclerosis in asymptomatic hypertensive subjects.